PENINGKATAN PRODUKTIVITAS TANAMAN PAKAN MELALUI PEMBERIAN FUNGI MIKORIZA ARBUSKULAR (FMA) - Nyimas Popi Indriani; Mansyur Mansyur; Iin Susilawati; Romi Zamhir Islami (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak)
Forage is needed by ruminant in large quantity. Several forages have low feed quality and then it is required to improve the forage quality that generally from gramineae and leguminoseae. Biotechnology using AMF is one of good strategic management on forage. AMF from the symbiotic mutualism with host plant through it’s root, has important role in plant production, ecosystem health. The best known mycorrhizal effect is that mycorrhizal plants take up more soil phosphorus and grow faster than corresponding non-mycorrhizal control plants. While spores are considered to be the resistant structure and may be viewed as ‘long term’ propagules when viable host plants are not present, hyphae are considered to be the main source of inokula when host plants are present and the soil is not disturbed.